Glucose‐6‐phosphate dehydrogenase deficiency is more prevalent in Duffy‐null red blood cell transfusion in sickle cell disease. Issue 3 (19th January 2022) - Yee, Marianne E.; Francis, Richard O.; Luban, Naomi L. C.; Easley, Kirk A.; Lough, Christopher M.; Roback, John D.; Josephson, Cassandra D.; Fasano, Ross M.
Abstract: Background: Resistance to malaria infection may be conferred by erythrocyte genetic variations including glucose‐6‐phosphate dehydrogenase (G6PD) deficiency and lack of Duffy antigens. In red blood cell (RBC) transfusion, G6PD deficiency may shorten transfusion survival. Because Duffy‐null units are commonly transfused in sickle cell disease (SCD) due to antigen matching protocols, we examined whether Duffy‐null donor RBC units have a higher prevalence of G6PD deficiency. Materials and methods: Pediatric patients with SCD on chronic transfusion therapy were followed prospectively for multiple transfusions. RBC unit segments were collected to measure G6PD activity and RBC genotyping. The decline in donor hemoglobin (ΔHbA) following transfusion was assessed from immediate posttransfusion estimates and HbA measurements approximately 1 month later. Results: Of 564 evaluable RBC units, 59 (10.5%) were G6PD deficient (23 severe, 36 moderate deficiency); 202 (37.6%) units were Duffy‐null. G6PD deficiency occurred in 40 (19.8%) Duffy‐null units versus 15 (4.5%) Duffy‐positive units ( p  < .0001). In univariate analysis, the fraction of Duffy‐null RBC units per transfusion was associated with greater decline in HbA ( p  = .038); however, in multivariate analysis, severe G6PD deficiency ( p  = .0238) but not Duffy‐null RBC ( p  = .0139) were associated with ΔHbA. Conclusion: Selection of Duffy‐null RBC units may result in shorter in vivo survival of transfused RBCs due to a higher likelihood of transfusing units from G6PD deficient donors.